The Environmental Drivers of Benthic Fauna Diversity and Community Composition - Saeedi, Hanieh; Warren, Dan; Brandt, Angelika (Frontiers in Marine Science, 2022)
Establishing management programs to preserve the benthic communities along the NW Pacific and the Arctic Ocean (AO) requires a deep understanding of the composition of communities and their responses to environmental stressors. In this study, we thus examine patterns of benthic community composition and patterns of species richness along the NW Pacific and Arctic Seas and investigate the most important environmental drivers of those patterns. Overall we found a trend of decreasing species richness toward higher latitudes and deeper waters, peaking in coastal waters of the eastern Philippines. The most dominant taxa along the entire study area were Arthropoda, Mollusca, Cnidaria, Echinodermata, and Annelida. We found that depth, not temperature, was the main driver of community composition along the NW Pacific and neighboring Arctic Seas. Depth has been previously suggested as a factor driving species distribution in benthic fauna. Following depth, the most influential environmental drivers of community composition along the NW Pacific and the Arctic Ocean were silicate, light, and currents. For example, silicate in Hexactinellida, Holothuroidea, and Ophiuroidea; and light in Cephalopoda and Gymnolaemata had the highest correlations with community composition. In this study, based on a combination of new samples and open-access data, we show that different benthic communities might respond differently to future climatic changes based on their taxon-specific biological, physiological, and ecological characteristics. International conservation efforts and habitat preservation should take an adaptive approach and apply measures that take the differences among benthic communities in responding to future climate change into account. This facilitates implementing appropriate conservation management strategies and sustainable utilization of the NW Pacific and Arctic marine ecosystems.